THE ANALYSIS OF SUPPLIER SELECTION ACTIVITIES ON FRESH FOOD SUPPLY CHAIN IN BANDUNG MART - Lesmana, Haris; Yudoko, Gatot (Journal of Business and Management, 2017)
Abstract. Background: Supplier is considered one of the most important aspects of running a business. To have a top supplier, the first step company needs to do is to have a proper supplier selection process. The object studied in this research is the vendor selection process of one retail company in Bandung, Indonesia; under the disguised name of Bandung Mart. In Bandung Mart, several suppliers often have hard times to keep up with Bandung Mart’s demand in the middle of the journey, while at the selection process they seem to be capable enough to meet Bandung Mart’s demand. Bandung Mart needs a method of quantification and calculation to justify and support the decision in selecting the supplier. Methods: This research follows the basic research procedure which consists of problem identification, literature review, data collection, data analysis, and conclusion and recommendation. In this case, the author selects weighted-point as the most suitable method to be implemented in Bandung Mart. Results: By using the weighted-point method, the most preferred supplier is generated. The manager is satisfied with the accuracy of the result. Conclusion: Each method has its advantages and disadvantages. The company needs to pick the most suitable method following company's condition. Keywords:  fresh food, retail, supplier selection, supply chain, weighted-point